2003
DOI: 10.1902/jop.2003.74.8.1183
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Interleukin‐1 Genotype and Periodontal Disease in a Diabetic Population

Abstract: These data confirm the high prevalence and severity of periodontitis in the diabetic population, and support the association between poor glycemic control and periodontal disease. The low prevalence of some of the IL-1 gene polymorphisms in the ethnic groups included in this study limits the validity of conclusions on genotype associations with clinical findings, but there was a trend suggesting that allele 1 at IL-1B (-511) and IL-1B (+3954) was overrepresented among diabetics with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 25 publications
4
65
0
14
Order By: Relevance
“…81 Evidence of a direct association between DM and periodontitis has been reviewed in the literature. 82 Significant correlations between periodontal disease parameters and poor glycaemic control have been demonstrated 83,84 and other reports of a reciprocal relationship between periodontal disease and glycaemic control. 85,86 Cross sectional studies on Pima Indians representing uncontrolled disease displayed the highest global prevalence of type 2 DM demonstrating an odds ratio of 2.8 to 3.4 for developing periodontal disease in type 2 DM compared with non-diabetic controls.…”
Section: An Overview Of Periodontitis and Dmmentioning
confidence: 93%
“…81 Evidence of a direct association between DM and periodontitis has been reviewed in the literature. 82 Significant correlations between periodontal disease parameters and poor glycaemic control have been demonstrated 83,84 and other reports of a reciprocal relationship between periodontal disease and glycaemic control. 85,86 Cross sectional studies on Pima Indians representing uncontrolled disease displayed the highest global prevalence of type 2 DM demonstrating an odds ratio of 2.8 to 3.4 for developing periodontal disease in type 2 DM compared with non-diabetic controls.…”
Section: An Overview Of Periodontitis and Dmmentioning
confidence: 93%
“…Periodontal parameters examined have included gingivitis, clinical attachment loss, and alveolar bone loss (Tomar & Asma, 2000). Studies have shown a relationship between poor glycemic control and periodontal disease parameters (Cutler et al, 1999;Guzman et al, 2003;Tervonen et al, 1994;Tsai et al, 2002). Finally, studies have been done which suggest that poorly controlled diabetics respond less successfully to periodontal therapy relative to well-controlled and non-diabetics (Westfelt et al, 1996;Tervonan & Karjalainen, 1997).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Periodontitis involves multiple clinical patterns including various severities of periodontitis, uncommon early onset forms that affect children and young adults with type 1 DM, and patients who do not respond predictably to conventional therapy refractory periodontitis. Guzman et al 71 have shown a possible interactions between genetic an enviromental factors that there is interplay between genetic an environmental factors that results in periodontal disease. The finding that a specific genotype in the IL-1 gene cluster correlates with severe periodontitis suggest a genetic mechanism by which some individuals, if challenged by bacterial accumulations, may have a more vigorous immuno-inflammatory response leading to more severe periodontitis in type 1 DM.…”
Section: Genetic Predisposition and Periodontal Disease In Type 1 Dmmentioning
confidence: 99%